Changes in sperm metabolites of Dezhou donkey after cryopreservation. Issue 12 (10th September 2022) - Yu, Jie; Wang, Zhaofei; Wang, Fuwen; Wang, Wenhao; Ge, Shihao; Fan, Zhaobin; Liu, Bing; Li, Min; Dong, Boying; Zhao, Fuwei; Dang, Ruihua
Abstract: Sperm cryopreservation technology has laid the foundation for promoting the popularity of artificial insemination in donkey reproduction, but the freeze–thaw process can cause sperm damage, and the viability of frozen sperm is greatly reduced, resulting in low insemination ability. Sperm metabolites play an important role in the freezing process of spermatozoa and have a major influence on the freezability of spermatozoa. The aim of this study was to explore the differential metabolites in donkey spermatozoa before and after cryopreservation by liquid chromatography–tandem mass spectrometry (LC–MS/MS). We analysed ejaculate samples from male donkeys obtained before and after freezing and identified 1323 metabolites. Compared with fresh sperm (F), the metabolites of cryopreserved sperm (CRY) were significantly changed, and 570 metabolites were significantly different between the two groups ( p  < .05). Among them, 277 metabolites were higher in frozen sperm, while the opposite was true for 293 metabolites. These metabolites mainly include phospholipids, lysophospholipids and amino acids., most of which are associated with oxidative stress and sperm capacitation. We describe significantly different metabolites before and after freezing that are significantly associated with decreased sperm motility post‐freezing and can be used as biomarkers of decreased sperm motility post‐freezing.